Analisis Pengujian Statis pada Rangka Kendaraan Listrik Niaga Roda Tiga dengan Metode Elemen Hingga - Zain, Alex Taufiqurrohman; Alamussofiyullah, Alamussofiyullah; Suranto, Dwi Djoko (P3M Politeknik Negeri Cilacap, 2025)
The frame is an important component in the automotive industry. With the development of computer systems, structural frame testing can be carried out by simulation. ANSYS Workbench is a popular program for static testing of frames. This research analyzes the parameters of equivalent stress, total deformation, and safety factors in the ladder frame of three-wheeled electric vehicles. Analyzing these three parameters is expected to provide an overview of the maximum load the frame can receive. The materials used are aluminum alloy and carbon steel, and the vertical load is 215 Kg (2,107 Newton) and 265 Kg (2,597 Newton). The results show that both materials can accept variations in the vertical load given, as seen from these three parameters. In more detail, carbon steel has better quality than aluminum alloy. Carbon steel produces the highest maximum equivalent stress value of 29,175 MPa and 35.96 MPa, and the lowest maximum total deformation values are 0.098137 mm and 0,12096. The minimum safety factor values for carbon steel are 10,06 and 8,1619.